Game Edukasi Untuk Pembelajaran IPA SMP Kelas VIII Berbasis Android - Hamria Hamka Hamria Hamka (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Educational games are one of the most effective learning aids that aim to provoke students' interest in learning to understand the learning material so that feelings of joy, happiness and not boring appear. The purpose of this research is to help increase students' learning motivation and can help students understand the lesson faster and can learn anywhere and anytime. This application is packaged in the form of a game that will be applied to a smartphone. This application will be made on the Android platform using the Java programming language. System testing in this study using the black box method and UAT testing. Based on the results of the tests that have been carried out, it is known that the responses from respondents to the questionnaires distributed are quite good with a percentage of 71%, while the results of the UAT test on design indicators are 92%, convenience is 92% and efficiency is 91% so that aspects of system acceptance to users are presented 91 % with a Very Good scale.